2021
DOI: 10.1016/j.heliyon.2021.e06424
|View full text |Cite|
|
Sign up to set email alerts
|

Consumer preference, growth and profitability of African catfish (Clarias gariepinus) grown in treated and aerated wastewater fed ponds in Kumasi, Ghana

Abstract: Recycling of wastewater provides a substantial solution to the global issue of water scarcity and high water use in aquaculture. However, this sustainable way of wastewater use has not been given much attention and exploration. This study focused on the consumer preference for fish grown in treated wastewater as well as the effect of aeration on the growth performance and economic benefit of African catfish (Clarias gariepinus) grown in treated wastewater. Two hundred (200) respondents from two communities (Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The principal mechanisms for fecal bacteria removal in maturation ponds are time and temperature, high pH (> 9) and high light intensity, combined with high dissolved oxygen concentration (Mara 2004;Kayombo et al 2010). The use of paddle-wheel aerators at times of low oxygen levels can significantly support fish production (Sey et al 2021) but should be solar-powered to avoid increased operational costs.…”
Section: Treated Wastewater Aquaculture Production Systemsmentioning
confidence: 99%
See 4 more Smart Citations
“…The principal mechanisms for fecal bacteria removal in maturation ponds are time and temperature, high pH (> 9) and high light intensity, combined with high dissolved oxygen concentration (Mara 2004;Kayombo et al 2010). The use of paddle-wheel aerators at times of low oxygen levels can significantly support fish production (Sey et al 2021) but should be solar-powered to avoid increased operational costs.…”
Section: Treated Wastewater Aquaculture Production Systemsmentioning
confidence: 99%
“…From a consumer perspective in both countries, no negative response related to wastewater-fed fish cultivation has been reported. Consumer surveys conducted, for example, in 2014 and 2018 in Kumasi (Ghana) showed that product attributes that influence consumers' fish-buying decisions were related to product price, size and perceived fish quality while the source of the fish was among the least important product attributes (Gebrezgabher et al 2015;Sey et al 2021), similar to results from Nigeria (Adeola et al 2016) or the purchase of potentially wastewater-irrigated vegetables (Keraita and Drechsel 2015). In Ghana, where the irrigation water in and around cities is severely polluted, the limited interest in the water source has been attributed to low education and health risk awareness (Drechsel and Keraita 2014).…”
Section: Selected Business Casesmentioning
confidence: 99%
See 3 more Smart Citations